Therapeutic Decision Making in a New Drug Era in Multiple Sclerosis - Keegan, B. Mark (Seminars in Neurology, 2013)
Multiple sclerosis is a presumed autoimmune, inflammatory disease of the central nervous system. Since the early 1990s, medications have been devised, tested, and approved for relapsing forms of multiple sclerosis (MS). MS treatments work by altering the immune system to reduce inflammatory MS activity, thus curtailing clinical relapses (attacks), thereby reducing short-term disability related to the MS attacks. The promise of long-term improvement in MS-related disability remains the most desirable therapeutic goal; to what degree current MS therapies are effective in reducing this is controversial. Recent years have seen a surge in novel MS therapies delivered both parenterally and orally that offer new therapeutic alternatives to MS patients and their treating providers. It remains essential to make an unequivocal diagnosis of MS and identify its clinical course prior to initiating therapies. Switching and altering MS therapies can now be done by rational approaches based on therapeutic efficacy and tolerability; however, these remain nonevidence-based for the most part. The high cost of MS therapies remains a significant concern. A new therapeutic era is at hand offering new hope for patients affected by this chronic, frequently disabling disease.
Keywords: multiple sclerosis (MS); diagnosis; therapy